PERLOKUSI DALAM FILM DO YOU BELIEVE KARYA JONATHAN M.GUNN (SUATU ANALISIS PRAGMATIK) - Kambey, Marco Fatski Samalo; Pelealu, Hetty; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  The title of this research is â€œPerlocution in the Film Do You Believe by Jonathan M.Gunn (A Pragmatic Analysis)â€ and it is intended as a requirement to accomplish a degree at the Faculty of Humanities Sam Ratulangi University. The aims of this study are to identify and classify the types of perlocution and to analyze and describe the meanings of perlocution in the film Do You Believe. Theories from a few experts are applied in this study, such as theory from Austin (1962) to unfold the meaning of perlocution in general and theory from Leech (1983) to unfold the categorization of 15 aspects of perlocution. The results show that there are some aspects of perlocutionary such as get hearer to know, persuade, encourage, irritate, frighten, amuse, get hearer to do, inspire, impressed, get hearer to talk, distract attention, attract attention, bore, deceive, embarrass.Keywords: Perlocution, Linguistic, film Do You Believe